2001
DOI: 10.3171/foc.2001.11.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Epidural motor cortex stimulation with functional imaging guidance

Abstract: Chronic epidural motor cortex stimulation (MCS) has been shown to have promise in the treatment of patients with refractory deafferentation pain. Precise placement of the electrode over the motor cortex region corresponding to the area of pain is essential for the success of this procedure. Whereas standard anatomical landmarks have been used in the past in conjunction with image guidance, the use of functional brain imaging can be beneficial in the precise surgical planning. The authors report the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…in a study of 5 patients with chronic pain conditions, and reported that integration of functional and anatomical imaging data allows for precise and efficient surgical planning and may reduce the time necessary for intraoperative physiological verification. [73] In clinical settings where technology is not available, is expensive, or is not affordable, Velasco et al . recommends a good MRI imaging technique and a reliable iCM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in a study of 5 patients with chronic pain conditions, and reported that integration of functional and anatomical imaging data allows for precise and efficient surgical planning and may reduce the time necessary for intraoperative physiological verification. [73] In clinical settings where technology is not available, is expensive, or is not affordable, Velasco et al . recommends a good MRI imaging technique and a reliable iCM.…”
Section: Discussionmentioning
confidence: 99%
“…[531657592109115] Chronic pain management surgical teams are becoming familiar with MCS, and this therapy is appearing in worldwide reports in the current literature. [121319252963738084909194105107119122] The author presents an updated literature review on the treatment of FCNP with MCS.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of neuropathic pain treatment with MCS varies from 15 to 90%, relative to the group at hand, with the best results achieved in the NFP group. Accordingly, the follow-up period may influence the outcome, as up to 40% of patients lose the positive effect of stimulation over a year [6,13,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Relieved one patient who developed CCP after removal of a spinal tumor (VAS 2) but not a syringomyelia CCP case [11] Mogilner and Rezai Stimulated one SCI but it is not clear whether this drew benefit [14] Present authors Treated two patients with CCP: one, who was propofol-negative, was a failure. The second one, a syringomyelia case, responded to parietal cortex stimulation for about 2 months and was a partial propofol-responder.…”
Section: Group Findingsmentioning
confidence: 93%